The Geometric Literacy Through the Missouri Mathematics Project Model Assisted by the Teachmint Application - Koimatul Chasanah; Iwan Junaedi (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study aims to examine the quality of the Missouri Mathematics Project (MMP) learning model assisted by the Teachmint application on students' geometric literacy. Geometric literacy is part of mathematical literacy related to understanding geometric concepts in everyday life. This study uses a mixed method with a sequential explanatory design. Quantitative data were collected through geometric literacy tests and analyzed using statistical tests, while qualitative data were obtained from observations and interviews. The experimental class in this study was Class X E-8, while the control class was Class X E-9. The results showed that the quality of learning at the planning stage obtained a very valid category with an average device validation of 88.73%. At the implementation stage, the implementation of learning showed very good results with an average teacher activity of 85.6% and student activity of 83.3%. The learning evaluation showed that the MMP model assisted by Teachmint was effective in improving geometric literacy, with the average final score of students exceeding the Learning Objective Achievement Criteria, the proportion of classical completeness reaching 90%, and an increase in students' geometric literacy by 62%. These findings confirm that the integration of structured practice-based learning models with digital technologies such as Teachmint can significantly improve the quality of students' mathematics learning and geometric literacy.